Прийоми емоційно-експресивного використання діалектних фразеологічних одиниць у художніх текстах - Дехтярьова, О. (Лексикографічний бюлетень, 2011)
The article considers the usage of dialect phraseological units in artistic texts as means of increasing text expressiveness. Scientists are much interested in studying phraseological fund taken from the artistic texts of the authors as bearers of dialectal speech at the end of XX – beginning of XXI centuries. Basic emotional and expressive ways of dialect phraseological unit’s usage in artistic texts are determined. Dialectal phraseological units proved to be means of intensification of expressiveness in description of characters, making the autor’s language more lively and reflecting ethnic peculiarity.